Pengaruh Kualitas Produk, Kualitas Layanan Dan Kepercayaan Pelanggan Terhadap Loyalitas Pelanggan (Survei Pada Pelanggan Kopi Kampoeng Jl. Raya Dermo No. 87 Dau Malang) - David Mujibur Rohman; Budi Wahono; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis study aims to determine the effect of product quality, service quality and trust on customer loyalty, the sample of this study were customers from Kampoeng coffee shops. Data collection using a questionnaire, data analysis using validity test, reliability test, normality test, multiple linear analysis, F statistic test and t statistic test, coefficient of determination test in IBM Social Sciences Statistical Package (SPSS) Version 16.0From the results of calculations with SPSS which are variables of product quality, service quality, trust have a simultaneous and significant effect on customer loyalty. While partially the variables of product quality, service quality and customer trust have a positive and significant effect on customer loyalty. Keywords: Quality Of Product, Quality Of Service Customer Trust Customer Loyalty